1251. Prevention of Pneumocystis Pneumonia by Ibrexafungerp in a Murine Prophylaxis Model. (31st December 2020) - Borroto-Esoda, Katyna; Azie, Nkechi; Ashbaugh, Alan; Cushion, Melanie; Angulo, David A
Abstract: Background: Pneumocystis pneumonia (PCP) is an opportunistic fungal infection that affects immunocompromised patients. Ibrexafungerp (IBX) is an oral and intravenous antifungal from a novel class of glucan synthase inhibitors, triterpenoids, and has shown activity against Candida, Aspergillus, and PCP in a murine therapy model. We evaluated the ability of IBX to prevent PCP in a prophylaxis model of murine PCP. Methods: Experiment 1: Balb/c mice (10 mice/group) were infected by intranasal inoculation with Pneumocystis murina, immune-suppressed with dexamethasone in acidified drinking water and treated with 30-, 15- and 7.5 mg/kg, IBX/BID. Control groups treatment included TMP-SMX (50/250 mg/kg QD) and vehicle. After 6 weeks, mice were sacrificed, and prevention was determined by organism burdens (asci and total nuclei). Experiment 2 : Balb/c mice were immune-suppressed and infected as in Exp. 1. Treatment groups included: 1) 30 mg/kg BID x 6wk; 2) 30 mg/kg/BID x 6wk followed by cessation of treatment with IBX but with immune-suppression for 3 additional weeks; 3) 15 mg/kg BID 1 week prior and 6 wks after infection and immune suppression; 4) 15mg/kg BID for 8 wks; 5) 15 mg/kg BID for 6 wks then IBX was discontinued but with immune suppression; 6) untreated, vehicle control. Results: Experiment 1: No P. murina nuclei or asci were observed after 6 weeks of treatment at a dose of 30 mg/kg/BID in the prophylaxis mouse model of PCP, similar to positive control, TMP/SMX. Some nuclei and asci were observed in the lower dose IBX groups. Experiment 2: To investigate whether any P. murina remained after different regimens of prophylaxis, treatment of IBX was withdrawn at both doses for an additional 3 wks of immune suppression to provoke the growth of any remaining fungi. Group 1 showed reduction in total nuclei and asci to undetectable. Group 2 did not result in any recrudescence of infection. Group 3 and 4 showed similar reduction in organism burden. Group 5 was similar to untreated control. Conclusion: These results demonstrate that 30 mg/kg BID IBX prevented PCP in a murine model. We suggest that IBX could be a viable option for preventing PCP in immunocompromised patients. Disclosures: Katyna Borroto-Esoda, PhD, SCYNEXIS, Inc. (Employee, Shareholder) Nkechi Azie, MD, SCYNEXIS, Inc. (Employee, Shareholder) Alan Ashbaugh, PhD, SCYNEXIS, Inc. (Grant/Research Support) Melanie Cushion, PhD, SCYNEXIS, Inc. (Grant/Research Support) David A. Angulo, MD, SCYNEXIS, Inc. (Employee, Shareholder)